2022
DOI: 10.3390/jof8050530
|View full text |Cite
|
Sign up to set email alerts
|

Sorbicillinoid Derivatives with the Radical Scavenging Activities from the Marine-Derived Fungus Acremonium chrysogenum C10

Abstract: Sorbicillinoids are a class of structurally diverse hexaketide metabolites with good biological activities. To explore new structural sorbicillinoids and their bioactivities, the marine-derived fungus Acremonium chrysogenum C10 was studied. Three new sorbicillinoid derivatives, acresorbicillinols A–C (1–3), along with five known ones, trichotetronine (4), trichodimerol (5), demethyltrichodimerol (6), trichopyrone (7) and oxosorbicillinol (8), were isolated. The structures of new sorbicillinoids were elucidated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…A recent study indicated that sorbicillinoid derivatives from marine-derived fungus also possessed radical scavenging activities. In the last four years, 69 new sorbicillinoids were identified from fungi [ 155 , 156 ]. Dimethyl incisterol A3 ( 338 ) and (l7 R )-17-methylincisterol ( 339 ) were obtained from a soft coral-derived fungus Talaromyces sp.…”
Section: Lactonesmentioning
confidence: 99%
“…A recent study indicated that sorbicillinoid derivatives from marine-derived fungus also possessed radical scavenging activities. In the last four years, 69 new sorbicillinoids were identified from fungi [ 155 , 156 ]. Dimethyl incisterol A3 ( 338 ) and (l7 R )-17-methylincisterol ( 339 ) were obtained from a soft coral-derived fungus Talaromyces sp.…”
Section: Lactonesmentioning
confidence: 99%
“…Trichodimerol ( 5 ) is a unique cage-like dimeric sorbicillinoid with a bright yellow color. Trichodimerol has been frequently isolated from various fungi ,, and displays potent antitumor activities; , nevertheless, whether its formation is enzymatic or spontaneous is still subject to debate. We found that the sponge-derived fungus Stagonospora sp.…”
Section: Introductionmentioning
confidence: 99%
“…14 Recently, three cage-like bisorbicillinoids, especially acresorbicillinol C (4) with strong DPPH radical scavenging activity, were isolated, and the sorbicillinoid biosynthetic gene cluster (Acsor BGC) was identified from Acremonium chrysogenum (Figure 2A). 18 Acsor BGC consists of two PKS genes (AcsorA and AcsorB) that are responsible for the backbone formation of sorbicillinoids. In addition, the cluster contains genes encoding an FMO (AcsorC), a BBE-like oxidase (AcsorD), a transporter (AcsorT), two regulators (AcsorR1 and AcsorR2), and one putative serine hydrolase (AcsorE).…”
mentioning
confidence: 99%
“…To trace the origin of the oxygen atom in reactions catalyzed by AcsorC and AcsorD, we incubated 2a with AcsorC in 18 O 2saturated buffer, and the molecular weight of the generated 1 increased by 2 amu, indicating incorporation of 18 O into 1. When 1 was further incubated with AcsorD, the molecular weight of the generated 3 increased by 2 amu, suggesting no incorporation of 18 O into 3 from 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation